1)=(по основанию 5) log(4+x)(1+2x)= log 9 4+x>0 x>-4 и 1+2x>0 x>-1/2, т е х>-1/2 4+8x+x+2x²=9 2x²+9x-5=0 x1,2=((-9+-√(81+40))/4= (-9+-11)/4, x1=-5-не удовлетворяет x>-1/2 x2=1/2-ответ 2) 1+x>0 x>-1и 2+x>0 x>-2, т е х>-1 = (по основанию 2)log(1+x)(2+x)=1 x²+x+2x+2=2, x²+3x=0 x1=0, x2=-3-не удовлетворяет x>-1 x=0- ответ 3) x-2>0 x>2 и x+1>0 x>-1, т е x>2 = (по основанию 2)log(x-2)(x+1)=2, x²+x-2x-2=4, x²-x-6=0, x1,2=(1+-√(1+24))/2=(1+-5)/2, x=3- ответ
3x+4>0⇒x>-4/3 U x>0 U x≠1
x∈(0;1) U(1;∞)
log(5)√(3x+4)*1/log(5)x=1
log(5)√(3x+4) = log(5)x
log(5)√(3x+4)-log(5)x=0
log(5)√(3x+4)/x=0
√(3x+4)/x=1
√(3x+4)=x
3x+4=x²
x²-3x-4=0
x1+x2=3 U x1*x2=-4
x1=-1∉ОДЗ
x2=4